Perioperative Exhaled Nitric Oxide as an Indicator for Postoperative Pneumonia in Surgical Lung Cancer Patients: A Prospective Cohort Study Based on 183 Cases - Gui-Xian Liu; Yue Yang; Lei Chen; Mi-Qi Gu; Jin-Tao He; Xin Wang (Canadian Respiratory Journal)
Introduction. This study is conducted to investigate the correlation between perioperative fractional exhaled nitric oxide and postoperative pneumonia (POP) and the feasibility of perioperative FeNO for predicting POP in surgical lung cancer patients. Methods. Patients who were diagnosed with non-small-cell lung cancer (NSCLC) were prospectively analyzed, and the relationship between perioperative FeNO and POP was evaluated based on patients’ basic characteristics and clinical data in the hospital. Results. There were 218 patients enrolled in this study. Finally, 183 patients were involved in the study, with 19 of them in the POP group and 164 in the non-POP group. The POP group had significantly higher postoperative FeNO (median: 30.0 vs. 19.0 ppb, P<0.001) as well as change in FeNO (median: 10.0 vs. 0.0 ppb, P<0.001) before and after the surgery. For predicting POP based on the receiver operating characteristic (ROC) curve, a cutoff value of 25 ppb for postoperative FeNO (Youden’s index: 0.515, sensitivity: 78.9%, and specificity: 72.6%) and 4 ppb for change in FeNO (Youden’s index: 0.610, sensitivity: 84.2%, specificity: 76.8%) were selected. Furthermore, according to the bivariate regression analysis, FEV1/FVC (OR = 0.948, 95% CI: 0.899–0.999, P=0.048), POD1 FeNO (OR = 1.048, 95% CI: 1.019–1.077, P=0.001), and change in FeNO (OR = 1.087, 95% CI: 1.044–1.132, P<0.001) were significantly associated with occurrence of POP. Conclusions. This prospective study revealed that a high postoperative FeNO (>25 ppb), as well as an increased change in FeNO (>4 ppb), may have the potential in detecting the occurrence of POP in surgical lung cancer patients.